Republic of Guinea : Socioeconomic Impact of Ebola Using Mobile Phone Survey - World Bank Group (World Bank, Washington, DC, 2016)
The Ebola pandemic has been one of the most virulent pandemics in modern times. By the end of 2015, the epidemic had cost the lives of more than 11,300 people in Guinea, Liberia, and Sierra Leone, including more than 500 frontline health care workers. After good growth performance between 2011 and 2013, Guinea’s economy has suffered a number of setbacks, including the Ebola crisis and a sharp drop in new investment in the mining sector. As part of the international effort to understand and manage the Ebola crisis and to obtain microeconomic data, the World Bank partnered with Guinea’s National Institute of Statistics (INS) to conduct a mobile phone survey to measure the socioeconomic impact of Ebola on households, following in the footsteps of similar mobile surveys conducted in Liberia and Sierra Leone in 2015. The study finds that the pandemic had ripple effects on the economic fabric and that the economic effects of Ebola have outlasted the epidemiological ones. In addition to the great loss of life, the epidemic has caused great damage to the countries’ economies. As part of the international response, the World Bank Group has significantly financed the Ebola-affected countries. Guinea was significantly affected by the Ebola pandemic, jeopardizing some of the gains in macroeconomic stability and poverty reduction during the last few years. The survey was conducted in all provinces of Guinea, with 60 percent of the respondents residing in the areas strongly affected by Ebola. Using newly collected data through a mobile phone survey, this study analyzes the socioeconomic impact of Ebola on households in Guinea. The survey shows that all parts of Guinea were economically affected by Ebola, with greater impacts in the southeast and the areas around Conakry. It is interesting to note that a quarter of respondents in the severely affected areas reported experiencing proven cases of Ebola in their neighborhood or village. In relation to agriculture, it is found that Ebola did not negatively affect agricultural production and food price. Another surprising finding is that despite Ebola and risk of contamination, households that needed treatment for malaria and diarrhea still visited a health facility, whereas a significant proportion of households reduced their attendance of health facilities. Income loss for rural households was much more related to difficulties in selling their production, than to lower agricultural production or lower food prices. However, Ebola has had a larger effect on urban employment, as illustrated by the increase in the urban unemployment rate. On the other hand, due to Ebola, children dropped out of school, and households adopted coping strategies by reducing their food consumption and selling key assets.